2000
DOI: 10.1093/ajcn/71.3.795
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and carotenoids plus vitamin E protect against ultraviolet light–induced erythema in humans

Abstract: The antioxidants used in this study provided protection against erythema in humans and may be useful for diminishing sensitivity to ultraviolet light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
160
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(180 citation statements)
references
References 20 publications
11
160
0
9
Order By: Relevance
“…The evaluation of a large number of associations could cause that significant results are chance findings. Previous intervention studies showed both positive effects of supplementation of either b-carotene or a combination of carotenoids on UV sensitivity (MathewsRoth et al, 1972;Gollnick et al, 1996;Lee et al, 2000;Stahl et al, 2000) or no effect on UV sensitivity (Wolf et al, 1988;Garmyn et al, 1995). The duration of the supplementation might be an important factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of a large number of associations could cause that significant results are chance findings. Previous intervention studies showed both positive effects of supplementation of either b-carotene or a combination of carotenoids on UV sensitivity (MathewsRoth et al, 1972;Gollnick et al, 1996;Lee et al, 2000;Stahl et al, 2000) or no effect on UV sensitivity (Wolf et al, 1988;Garmyn et al, 1995). The duration of the supplementation might be an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies were, however, inconclusive and contradictory (La Ruche and Cesarini, 1991;Werninghaus et al, 1994;Garmyn et al, 1995;Gollnick et al, 1996;Eberlein-König et al, 1998;Fuchs & Kern, 1998;Wolf et al, 1988;Lee et al, 2000;Stahl et al, 2000). Moreover, all these studies used synthetic (pure) compounds in relatively high dosages compared to the normal physiological range of vitamins and carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…Derg. 40(1): [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]2016 Şen 39 fotohasarın şiddetiyle orantılıdır. Tip IV kollagen dermoepidermal bileşkedeki temel kollajen olup mekanik etkileşim için büyük önem taşımaktadır.…”
Section: Yaşlanma Sonucu Deride Görülen Değişikliklerunclassified
“…In addition, they exhibit antioxidant, antimutagenic, anti-inflammatory and anticarcinogenic activities. Therefore, the use of botanicals is an approach to reduce the UV-generated ROS-mediated photodamage, immune-suppression and skin cancer in patients (Katiyar et al, 2000(Katiyar et al, , 1999Morales et al, 2011;Stahl et al, 2000;Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%